Odpowiedzi

Najlepsza Odpowiedź!
2010-02-07T15:37:05+01:00
2a(b-3)-2b(a-3)=2ab-6a-2ab+6b=6b-6a

a(a+b)+a(a-b)+b(b+a)=a²+ab+a²-ab+b²+ab=2a²+ab+b²

5a(a-2)+2a(a+5)=5a²-10a+2a²+10a=7a²

3(a+2b-3c)-2(a-2c)=3a+6b-9c-2a+4c=a+6b-11c

5(c-b)-(c+b)=5c-5b-c-b=4c+4b
2010-02-07T15:39:29+01:00
A)
2a(b-3)-2b(a-3) = 2ab-6a-2ab+6b = -6a+6b
b)
a(a+b)+a(a-b)+b(b+a) = a²+ab+a²-ab+b²+ab = 2a²+ab+b²
c)
5a(a-2)+2a(a+5) = 5a²-10a+2a²+10a = 7a²
d)
3(a+2b-3c)-2(a-2c) = 3a+6b-9c-2a+4c = a+6b-5c
e)
5(c-b)-(c+b) = 5c-5b-c-b = 4c-6b